2003
DOI: 10.1007/s00404-002-0465-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide production is not altered in preeclampsia

Abstract: Our study has demonstrated that there was no alteration in nitric oxide production in preeclampsia, thus contributing to the existing unresolved role of nitric oxide in the pathogenesis of preeclampsia. Further research is called for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Some earlier studies reported an increase of maternal NO in diabetes or preeclampsia [14,15] , whereas in one study [26] no alternation of NO production in preeclampsia was found. However, it seems that production of NO (or cGMP) and other vasodilators represents a compensatory and protective mechanism for variation of vasoconstrictors (including ET-1) production to maintain blood flow and limit platelet aggregation in the fetomaternal circulation [15] .…”
Section: Discussionmentioning
confidence: 83%
“…Some earlier studies reported an increase of maternal NO in diabetes or preeclampsia [14,15] , whereas in one study [26] no alternation of NO production in preeclampsia was found. However, it seems that production of NO (or cGMP) and other vasodilators represents a compensatory and protective mechanism for variation of vasoconstrictors (including ET-1) production to maintain blood flow and limit platelet aggregation in the fetomaternal circulation [15] .…”
Section: Discussionmentioning
confidence: 83%
“…HPLC analyses of plasma/serum nitrite and nitrate have been employed to ascertain a role for NO in the pathogenesis of endothelial dysfunction in pregnant women with preeclampsia [63]. The HPLC-DAN method has been used to determine changes in placental NO synthesis during various stages of ovine fetal development (0.29 to 1.66 nmol/h per g placentomal tissue between Days 30 and 140 of gestation) [64].…”
Section: Other Clinical Studiesmentioning
confidence: 99%
“…Altered normal hemodynamic response and endothelial dysfunction are major pathophysiological manifestations of this entity [3,4]. Reports related to nitric oxide (NO) secretion and preeclampsia are contradictory, some studies indicating altered production and/or activity [5][6][7][8][9][10][11], others not [12][13][14]. These contradictions are most likely due to differences in the research approach, the analyzed NO metabolites and/or the applied measuring methods.…”
Section: Introductionmentioning
confidence: 91%